Defining the Medical Imaging Requirements for a Rural Health Center - Borrás, Cari.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book establishes the criteria for the type of medical imaging services that should be made available to rural health centers, providing professional rural hospital managers with information that makes their work more effective and efficient. It also offers valuable insights into government, non-governmental and religious organizations involved in the planning, establishment and operation of medical facilities in rural areas. Rural health centers are established to prevent patients from being forced to travel to distant urban medical facilities. To manage patients properly, rural health centers should be part of regional and more complete systems of medical health care installations in the country on the basis of a referral and counter-referral program, and thus, they should have the infrastructure needed to transport patients to urban hospitals when they need more complex health care. The coordination of all the activities is only possible if rural health centers are led by strong and dedicated managers. The book also represents a valuable resource for those physicians, medical physicists and service engineers who provide virtual and physical consultations.
Part I Medical and Public Health Needs of a Rural Health Center -- Characteristics of a rural health center -- Medical imaging needs in a rural health center from a clinical point of view -- Part II: Medical Imaging Modalities -- Medical imaging equipment characteristics at the health center level: Overview -- Technical specifications -- Ultrasound units -- X-ray units Planar Radiography -- Part III: Planning a Medical Imaging Service -- Physical infrastructure and procurement issues -- Basic training and continuing education of technical staff in rural health centers - a personal view -- Teleradiology and networking -- Part IV: Operational Considerations -- Quality control, radiation protection and maintenance programs -- Patient referral to secondary and tertiary health care -- Recommendations -- Annex -- Appendices: Practical cases.
Keywords: Biomedical engineering; Biomedical Engineering and Bioengineering